PPK BUILDING A BEAUTY SALON BUSINESS: STRATEGIES FOR STRENGTHENING DIGITAL MARKETING AND BUSINESS MANAGEMENT FOR STUDENTS AND ALUMNI OF THE DEPARTMENT OF MAKEUP AND BEAUTY - Vivi Efrianova; Mitra Lusiana; Rahmi Oktarina3; Salma Taqwa (Journal of Community Service, 2024)
The Makeup and Beauty Department at FPP UNP is part of vocational education with a profile of graduates who are able to work in the world of business and industry (DUDI), continue their education to a higher level, and become entrepreneurs in the beauty sector. However, the results of the 2022-2023 Tracer Study show the low interest of TRK alumni in entrepreneurship and a lack of skills in digital marketing, management and business bookkeeping. Apart from that, the achievement and participation of TRK students in the PKMK UNP program is also still low. The Entrepreneurship Strengthening Program (PPK) in its first year in 2024 aims to increase the competency of students and alumni in managing beauty salon businesses. Achievement targets for the first year (2024) for partners: (1) Increase partner HR competency in line with developing trends, (2) master beauty salon business management and bookkeeping, (3) master digital marketing techniques, (4) be able to produce innovative beauty products, such as false eyelashes made from natural fibers from kepok banana stems with Halal Eyelash branding. The main output of the PPK Service Scheme is the formation of three new entrepreneurs consisting of two students and one TRK alumni. Program outputs include scientific articles, activity videos, electronic media articles, and ISBN books related to product innovation. This program supports UNP's strategy in the 2020-2025 Strategic Plan, focusing on community service and solutions to social problems.